Determinants of Poverty Rate in Eastern Indonesia - Soleman, Riky; Soleman, Risky (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2022)
Poverty is a global issue faced by many countries in the world, including Indonesia. The purpose of this study is to examine the level of poverty in Eastern Indonesia by measuring Islamic banking financing, economic growth, LFPR, education and health and inflation against poverty levels in Eastern Indonesia. The data source used in the form of panel data is obtained from the Central Statistics Agency (BPS) for the 2011-2021 period. Data analysis using regression panel data with Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM) approach processed with E-Views 10. The results of this study indicate that the estimated model chosen in this study is Random The Effect Model (REM) followed by LM testing shows that the results of the Islamic Banking Financing, TPAK, RLS, UHH, and Inflation variables have no significant effect in a negative direction on the poverty level. negative. This means, for example, that there are independent variables simultaneously, so that the poverty level in Eastern Indonesia is increasingly leading to change. Meanwhile, in the simultaneous test the F-Statistic prob value is 0.000000 < 0.05, which means that the six independent variables simultaneously affect the poverty level in Eastern Indonesia. And the value of Adjusted R-Square is 0.607420 which means 60% of the variables of Islamic Banking Financing, economic growth, TPAK, RLS, UHH, and Inflation in this study are able to explain the variation of economic growth variables. While the remaining 40% is explained by other variables outside the model.